2019
DOI: 10.5430/ijfr.v10n5p110
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Risk Disclosures: A Comparative Analysis Between Bangladeshi and Malaysian Islamic Banks

Abstract: Corporate governance provides a fundamental framework to oversee corporate conduct and ensures transparency of institutions like banks. In case of Islamic banks, it adds additional importance as the profit sharing (with the depositors) system enhances the chance of agency problem for such institutions. Again, risks are inherent in institutions like Islamic banks, which necessitate the investors to get proper information about the risk encountered by the banks in which they invest. Thus, corporate governance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Due to the function of the step, it has appeared throughout the five years. It is also worth noting that window dressing (Kabir et al, 2019) is also evident here. The example of the step can be seen in Example 2.1 which informs how the bank highlights RMF in guiding the risk management using its elements.…”
Section: Move 2: Risk Management Framework (Rmf)supporting
confidence: 59%
See 3 more Smart Citations
“…Due to the function of the step, it has appeared throughout the five years. It is also worth noting that window dressing (Kabir et al, 2019) is also evident here. The example of the step can be seen in Example 2.1 which informs how the bank highlights RMF in guiding the risk management using its elements.…”
Section: Move 2: Risk Management Framework (Rmf)supporting
confidence: 59%
“…However, a number of studies agreed that Islamic banks were prone to more risks due to their adherence to the shariah law (see Hemrit, 2019;Alam et al, 2018;Khan et al, 2017). The Malaysian Islamic banks showed better risk disclosures than the foreign Islamic banks (Kabir et al, 2019;Chong et al, 2019). Kabir et al (2019) found that the reports by the Malaysian Islamic banks were better than those reported in Bangladesh as the risk information in the latter indicated good governance.…”
Section: Risk Reportingmentioning
confidence: 99%
See 2 more Smart Citations
“…The topic of risk disclosure then became a topic of scrutiny among researchers. They conducted their studies on companies both in developed and developing countries, for example in the UK and Canada (Linsley et al, 2006;Linsley & Shrives, 2005) Saudi Arabia (Ahmad et al, 2017;Al-Maghzom et al, 2016;Moumen et al, 2015) Indonesia (Aryani, 2017;Mukhibad et al, 2020) Pakistan (Ashfaq et al, 2016), Malaysia and Bangladesh (Kabir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%